Fund-supported adjustment programs and economic growth - Khan, Mohsin S. 1946-; Knight, Malcolm Donald 1944- (Occasional papers, 1985)
This is the first of a group of papers dealing with various aspects of Fund-supported adjustment programs. The other two, The Global Effects of Fund-supported Adjustment Programs by Morris Goldstein and Fund-Supported Programs, Fiscal Policy, and Income Distribution by the Fiscal Affairs Department, will also be published in the Fund's Occasional Paper Series